DEVELOPMENT, DISPLACEMENT AND GENDER DISCRIMINATION: A STUDY ON DAM DISPLACED PEOPLE IN INDIA - Kumar, Sudesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
We are living in 21st century. Still gender discrimination exists in the society. It is the need of the hour to change the traditional laws due to which women are facing discrimination. Dam are considered as ‘temples of modern India’. But, unfortunately due to dam constructions millions of people have been displaced from their ancestral homeland. The displaced people have only been given monetary compensation according to Land Acquisition Act 1984. The main objective of the study is to examine how the displaced women face gender discrimination within and outside the family. According to R&R policy, they are considered as dependent family members. It has also been seen that the women are not only sidelined by the policy makers, but also confront adverse situations within the family. The displaced families share their compensation money with the male members, but women are totally ignored. As far as employment is concerned, the government also prefers to give employment to the male members of the family instead of females. Due to discrimination, the socio-economic life of displaced women gets tremendously affected. The study suggests that respective state government should prepare gender neutral policy, so that displaced women do not face any kind of socio-economic problems in their life.